Effect of Instructional Program on Knowledge Regarding Vulvovaginal Candidiasis Among Female University Students - Amel Dawod Kamel Gudia; Abeer Saad Eswi; Azza Ali Abd El hamid; Soumaya Mohamed Hassan (Indonesian Journal of Global Health Research, 2019)
Adolescents learn about Vulvo vaginal candidiasis (VVC) because its common clinical problem in female during this age throughout the world particularly in hot, subtropical climates. Annually in the United States there are approximately 13 million cases of vulvo vaginal candidiasis (VVC), resulting in 10 million gynecologic office visits per year. It is estimated that 75% of women will experience at least one episode in their lifetime, with a projected 50% of all female experiencing multiple episodes (Kamath, etal , 2014). Education in health is one of the key components of primary health care and one of the most vital health care requirements for female that must be considered much more in the primary health care system, particularly maternal and child health. Moreover Knowledge of how to prevent vaginal Candidiasis could save many female from frequent office visit, uncomfortable vaginal infections and prevent complications of it (Gilson, 2012). To assess the knowledge of female university students about (VVC) and examine the effect of instructional program on their knowledge regarding Vulvovaginal Candidiasis among female university students. A quasi-experimental design "time-series" will be utilized to achieve the aim of current study. The current study was conducted at Cairo University hostel were the female students were residing and selected from non medical faculties. A simple random sample of 100 female university students was recruited for this study. Two tools were used to collect the study data; structured interview tool, and "VVC" structured knowledge assessment interviewing tool. The current study findings revealed that, mean age of the participents was 20.18± 1.19 years. More than two thirds of them fell in the age range 20-24 years. Regarding menstrual characteristics among the participants, age range at menarche was 11-14 years with a mean of ± SD was (12.30±1.88) years, duration of menstruation ranged between 2-6 days with a mean of (4.23±1.25). The total mean knowledge score of (VVC) was 18.87 ± 7.83 out of /85 in the pretest; which indicated poor knowledge level and 81.20 ± 5.01 in posttest after two weeks from instruction program; which indicated good knowledge level that remain good knowledge in the post test ( 2) with a mean of 74.35± 6.68 after eight weeks from instruction program, and 62.85 ± 6.89 in the post test (3) after 12 weeks from weeks from instruction program; which indicated satisfactory knowledge level with high statistical significant differences (P = 0.001). The instructional program had positive effect on knowledge and awareness regarding (VVC) among female university students and this results hence the research hypotheses . Keywords- instructional program, vulvovaginal candidiasis, female university students